2017
DOI: 10.1111/coep.12215
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the Social Security Early Retirement Age

Abstract: Using a regression discontinuity framework, this paper documents a previously unnoticed drop of 7%-8% in the U.S. suicide rate upon reaching age 62 during 1990-2014. This decline is concentrated among men, nearly doubled in size over the most recent decade as the income gap between those just older and younger narrowed, and represents the only trend break among ages 45-79. These findings, along with the observed timing of retirement and benefit claims and research on how income affects suicide, suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Increasing Retirement benefits in the USA, South Korea and Chile,(n=5) Five studies in the review examined expansionary policy changes related to retirement benefits (Table 3). While two of these studies focused on changes to earnings-related contributory benefits in the US (Desimone, 2018;Golberstein, 2015), the remaining three studies, two in South Korea (Lee and Wolf, 2014;Pak, 2020) and one in Chile (García and Otero, 2017), evaluated the impact of expanding means-tested support aimed at reducing poverty among the low-income elderly.…”
Section: Increasing the Generosity Of Tax Credits In The Uk (N=2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing Retirement benefits in the USA, South Korea and Chile,(n=5) Five studies in the review examined expansionary policy changes related to retirement benefits (Table 3). While two of these studies focused on changes to earnings-related contributory benefits in the US (Desimone, 2018;Golberstein, 2015), the remaining three studies, two in South Korea (Lee and Wolf, 2014;Pak, 2020) and one in Chile (García and Otero, 2017), evaluated the impact of expanding means-tested support aimed at reducing poverty among the low-income elderly.…”
Section: Increasing the Generosity Of Tax Credits In The Uk (N=2)mentioning
confidence: 99%
“…However, such differences in results could be, at least partially, attributed to heterogeneity across the studies. For example, both of the J o u r n a l P r e -p r o o f studies that found positive effects focused on contributory retirement benefits, were based in the USA and focused on the effects on depression and suicide (Desimone, 2018;Golberstein, 2015). In contrast, the remaining three studies that investigated means-tested benefits for low-income elderly, were based in South Korea and Chile (García and Otero, 2017;Lee and Wolf, 2014), and evaluated effects on more general measures of subjective wellbeing, which suggests that the results of these studies are not directly comparable.…”
Section: Summary Of the Key Findingsmentioning
confidence: 99%
“…For example, suicide Open access rates in men in the USA fall sharply when individuals become eligible for social security retirement benefits, even though only a small fraction of men retire at this age. 8 Moreover, two major systematic reviews investigating the relationship between income and health in OECD countries also found that additional financial resources, including those from social security benefits, can have positive effects on both adult 9 and child mental health. 10 11 Lack of social protection, on the other hand, has been associated with negative effects on mental health.…”
Section: Introductionmentioning
confidence: 99%